American Jewish Year Book 2018 The Annual Record of the North American Jewish Communities Since 1899 - Dashefsky, Arnold; Sheskin, Ira M. (American Jewish Year Book,, 2019)
The American Jewish Year Book, now in its 118th year, is the annual record of the North American Jewish communities and provides insight into their major trends. The first two chapters of Part I include a special forum on "Contemporary American Jewry: Grounds for Optimism or Pessimism?" with assessments from more than 20 experts in the field. The third chapter examines antisemitism in Contemporary America. Chapters on "The Domestic Arena" and "The International Arena" analyze the year's events as they affect American Jewish communal and political affairs. Three chapters analyze the demography and geography of the US, Canada, and world Jewish populations. Part II provides lists of Jewish institutions, including federations, community centers, social service agencies, national organizations, synagogues, Hillels, day schools, camps, museums, and Israeli consulates. The final chapters present national and local Jewish periodicals and broadcast media; academic resources, including Jewish Studies programs, books, journals, articles, websites, and research libraries; and lists of major events in the past year, Jewish honorees, and obituaries. Today, as it has for over a century, the American Jewish Year Book remains the single most useful source of information and analysis on Jewish demography, social and political trends, culture, and religion. For anyone interested in Jewish life, it is simply indispensable. David Harris, CEO, American Jewish Committee (AJC), Edward and Sandra Meyer Office of the CEO The American Jewish Year Book stands as an unparalleled resource for scholars, policy makers, Jewish community professionals and thought leaders. This authoritative and comprehensive compendium of facts and figures, trends and key issues, observations and essays, is the essential guide to contemporary American Jewish life in all its dynamic multi-dimensionality. Christine Hayes, President, Association for Jewish Studies (AJS)and Robert F. and Patricia R. Weis Professor of Religious Studies in Classical Judaica at Yale University.